Cognitive Ability In Recognizing Colors Through Experimental Method In Children Aged 5-4 Years At RA Plus Fatahul Wardah Palembang - Syaputri, Mutia; Marlina , Leny; Oktamarina, Lidia (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study examines the development of children’s cognitive ability in recognizing colors through an experimental learning method in a Raudhatul Athfal (RA) setting. The research aims to describe the implementation of experimental-based color recognition activities and to analyze their contribution to cognitive and Islamic character development in children aged 4–5 years. A qualitative case study design was employed involving 15 children and one classroom teacher at an RA in Palembang over six weeks. Data were collected through classroom observations, semi structured interviews, and documentation, then analyzed using data reduction, display, and conclusion drawing. Findings indicate that experimental activities such as color mixing, observing color changes, and naming colors using concrete media enhanced children’s abilities to distinguish primary and secondary colors and improved aspects of perception, memory, and reasoning. The learning process also fostered holistic Islamic development, including discipline during activities, gratitude for Allah’s creations reflected in color diversity, and adab in collaborative exploration. The study highlights that experimental learning supports meaningful cognitive engagement while integrating Islamic values in early childhood education. These findings suggest that structured experimental activities can strengthen cognitive color recognition and promote holistic development in RA classrooms.